Isolation and Characterisation of Genes Expressed in Zygotic Embryos and Suspension Cultures of Oil Palm (Elaeis Guineensis Jacq.) - Namasivayam, Parameswari (2000)
The bottleneck of the current oil palm tissue culture technique is the low rate of embryogenesis and the development of viable embryoid lines. Therefore, it is vital to increase the efficiency of callusing, embryogenesis, germination and proliferation of embryoids so that the number of subcultures per line can be reduced without effecting the number of shoots produced in-vitro. Thus, it is necessary to elucidate and understand the molecular processes that are involved during somatic embryogenesis of oil palm particularly those involved in specifying embryogenic competence. Based on the role of cell division cycle (cdc/cdk) genes and cyclins in cell division cycle control of other eukaryotes, it is likely that cyclins are also partially involved in the regulation of somatic embryogenesis. Hence, an attempt to isolate cyclin genes from the oil palm zygotic embryo cDNA library was made using heterologous cyclin cDNA probes from Arabidopsis. 32 putative clones designated as OPZE, were isolated from screening. A preliminary characterisation was carried out on these clones in order to identify clones with sequences related to the cell division cycle. This was achieved by hybridising the peR amplified OPZE clones with amplified cDNA from suspension cultures and mature leaves separately. The OPZE clones were categorised into 3 subpopulations according to their tissue-specific expression pattern: a, b and c. Randomly selected clones from these subpopulations were sequenced partially and used for sequence homology searches using DNA sequence databases. Most clones did not have any significant homology to any known sequences in the database, thus they were designated as novel clones. Three clones OPZEJA, OPZE3A and OPZE5A that had significant homology to oleo sin, calmodulin and tumour suppressor protein respectively were selected for northern analysis. From the northern analysis studies, it was found that OPZEJA (oleosin) is zygotic embryo specific and both OPZE3A and OPZE5A are ubiquitously expressed in all evaluated tissues. In order to complement this study, a partial length homeobox gene, OPHbJ (KnottedJ -like) from oil palm was isolated and was found to be expressed specifically in meristematic tissues. However, the specific functions of these genes during oil palm embryogenesis are still unknown.